The Manila public secondary school teachers' salary schedule an appraisal of its implementation, 1971-1972 - Zulueta, Francisco M. 1930- (s.n.], 1972)
This study explored the provisions, extent of implementation, and implications of the salary schedule of secondary teachers in Manila. It employed the normative survey approach through documentary analysis. Findings showed that all provisions set in the salary schedule of secondary public school teachers of Manila are fully-implemented. It was concluded that teacher recruitment is not a grave personnel problem in the Division of City schools of Manila.